Influence of strong pulsed electric fields on vitamins in milk - Sviatnenko, Roman; Marynin, Andriy; Kochubei-Lytvynenko, Oksana (My University, 2018)
The article presents the results of the study on changes in the content of vitamin C in processed milk by pulsed electric fields. The optimal processing modes are set.
Keywords: імпульсні електричні поля; молоко; pulsed electric field; milk; кафедра технології молока і молочних продуктів; кафедра технологічного обладнання та комп’ютерних технологій проектування